Bovine colostrum supplementation`s lack of effect on immune variables during short-term intense exercise in well-trained athletes - Carol, A.; Witkamp, R. F.; Wichers, H. J.; Mensink. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2011)
The purpose of this study was to investigate the potential of bovine colostrum to attenuate postexercise decline in immune function. The authors evaluated the time course of a number of immune variables after short-term intense exercise in 9 male athletes after 10 d of supplementation with either colostrum or skim-milk powder. To increase the stress on the immune system subjects performed a glycogen-depletion trial the evening before the endurance trial (90 min at 50% Wmax). Blood samples were taken before the glycogen-depletion trial, before and after the endurance trial, and the next morning, ~22 hr after cessation of the exercise. Plasma cortisol levels increased over time, reaching the highest level directly after exercise, and were still elevated ~22 hr after exercise compared with baseline values (p < .001). Neutrophil cell count was increased after exercise and dropped below starting values 22 hr after exercise (time effect p < .001). Circulating immunoglobulins did not change over time. A significant time effect was seen for interleukin (IL)-6, IL-10, IL-1-receptor agonist, and C-reactive protein, with levels being higher directly after exercise (p < .05). Other cytokines (interferon-Gamma, IL-1a, IL-8, tumor necrosis factor-a) did not show a time effect. No differences were seen between colostrum and skim-milk powder in any of the investigated variables. Our results are consistent with the hypothesis that intense exercise affects several variables of the immune system. Colostrum did not alter any of the postexercise immune variables compared with skimmilk powder, suggesting no role for bovine colostrum supplementation in preventing postexercise immune suppression after short-term intense exercise.